A Flexible a-SiC-Based Neural Interface Utilizing Pyrolyzed-Photoresist Film (C) Active Sites - Chenyin Feng; Christopher L. Frewin; Md Rubayat-E Tanjil; Richard Everly; Jay Bieber; Ashok Kumar; Michael Cai Wang; Stephen E. Saddow (Micromachines, 2021)
Carbon containing materials, such as graphene, carbon-nanotubes (CNT), and graphene oxide, have gained prominence as possible electrodes in implantable neural interfaces due to their excellent conductive properties. While carbon is a promising electrochemical interface, many fabrication processes are difficult to perform, leading to issues with large scale device production and overall repeatability. Here we demonstrate that carbon electrodes and traces constructed from pyrolyzed-photoresist-film (PPF) when combined with amorphous silicon carbide (a-SiC) insulation could be fabricated with repeatable processes which use tools easily available in most semiconductor facilities. Directly forming PPF on a-SiC simplified the fabrication process which eliminates noble metal evaporation/sputtering and lift-off processes on small features. PPF electrodes in oxygenated phosphate buffered solution at pH 7.4 demonstrated excellent electrochemical charge storage capacity (CSC) of 14.16 C/cm2, an impedance of 24.8 ± 0.4 kΩ, and phase angle of −35.9 ± 0.6° at 1 kHz with a 1.9 kµm2 recording site area.